2012
DOI: 10.5539/gjhs.v4n4p159
|View full text |Cite
|
Sign up to set email alerts
|

Health Promotion Education in India: Present Landscape and Future Vistas

Abstract: ‘Health promotion is the process of enabling people to increase control over and to improve their health’. This stream of public health is emerging as a critical domain within the realm of disease prevention. Over the last two decades, the curative model of health care has begun a subtle shift towards a participatory model of health promotion emphasizing upon practice of healthy lifestyles and creating healthy communities. Health promotion encompasses five key strategies with health communication and education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…In order to obtain the best available insights into the imparting of family medicine teaching in India, we adopted an iterative process. [ 14 ] A detailed internet search was carried out to identify family medicine courses. The websites of Association of Indian Universities, Indian Council of Medical Research, Universities Grants Commission, Medical Council of India (MCI), Indian Nursing Council, and Ministry of Health and Family Welfare were also searched.…”
Section: Methodsmentioning
confidence: 99%
“…In order to obtain the best available insights into the imparting of family medicine teaching in India, we adopted an iterative process. [ 14 ] A detailed internet search was carried out to identify family medicine courses. The websites of Association of Indian Universities, Indian Council of Medical Research, Universities Grants Commission, Medical Council of India (MCI), Indian Nursing Council, and Ministry of Health and Family Welfare were also searched.…”
Section: Methodsmentioning
confidence: 99%
“…Indian universities and schools have just begun to realize the need for introducing global health curricula. India currently has 398 medical colleges ( 3 ), but none of them have started imparting global health education to its students. The curriculum in the medical colleges of India at the undergraduate and postgraduate level lacks global perspectives of all health related issues.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed Internet search was carried out to identify global health courses using the Google search engine with “global health, global public health, international health, global issues, and universal health” as the key words. The websites of Association of Indian Universities, Indian Council of Medical Research, University Grants Commission, Medical Council of India, Dental Council of India, Indian Nursing Council, and Ministry of Health and Family Welfare were searched ( 3 ). A similar search in the websites of the Indira Gandhi National Open University (IGNOU), professional associations, namely, Indian Medical Association, Academy of Family Physicians of India, World Association of Family Doctors (WONCA), World Health Organization (WHO), and various public health institutes, corporate hospitals, and autonomous medical institutes, such as All India Institute of Medical Sciences (AIIMS), Christian Medical College (CMC), Vellore, Post Graduate Institute (PGIMER), Chandigarh, and Jawaharlal Institute of Post Graduate Medical Education and Research (JIPMER), Puducherry, were also carried out in October 2015.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present Indian medicine (MBBS) curriculum lacks health promotion component during formative training [ 19 ]. Evidence from earlier Indian studies on the student’s beliefs and practices of health promotion reported that most students assessed preventive practices in their patients but did not feel well prepared and competent enough to counsel patients about health issues [ 20 ]. Furthermore, physicians have not been trained in-service.…”
Section: Discussionmentioning
confidence: 99%